Use of High-Flow Nasal Cannula Oxygen Therapy in a Pregnant Woman with Dermatomyositis-Related Interstitial Pneumonia - Tomohiro Shoji; Takeshi Umegaki; Kota Nishimoto; Natsuki Anada; Akiko Ando; Takeo Uba; Munenori Kusunoki; Kanako Oku; Takahiko Kamibayashi (Case Reports in Critical Care)
A 33-year-old pregnant woman was referred to our hospital with respiratory distress at 30 weeks of gestation. Chest computed tomography (CT) scans revealed pulmonary infiltrates along the bronchovascular bundles and ground-glass opacities in both lungs. Despite immediate treatment with steroid pulse therapy for suspected interstitial pneumonia, the patient’s condition worsened. Respiratory distress was slightly alleviated after the initiation of high-flow nasal cannula (HFNC) oxygen therapy (40 L/min, FiO2 40%). We suspected clinically amyopathic dermatomyositis (CADM) complicating rapidly progressive refractory interstitial pneumonia. In order to save the life of the patient, the use of combination therapy with immunosuppressants was necessary. The patient underwent emergency cesarean section and was immediately treated with immunosuppressants while continuing HFNC oxygen therapy. The neonate was treated in the neonatal intensive care unit. The patient’s condition improved after 7 days of hospitalization; by this time, she was positive for myositis-specific autoantibodies and was diagnosed with interstitial pneumonia preceding dermatomyositis. This condition can be potentially fatal within a few months of onset and therefore requires early combination immunosuppressive therapy. This case demonstrates the usefulness of HFNC oxygen therapy for respiratory management as it negates the need for intubation and allows for various treatments to be quickly performed.